SOCIOLOGICAL ANALYSIS OF QUALITY IN PUBLIC SERVICES AND THEIR IMPACT ON SOCIAL WELL-BEING - Kamila Yu. Utsumieva (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a view on the connection between social well-being and the quality of the public services offered.